An investigation study of gelatin release from semi‐interpenetrating polymeric network hydrogel patch for excision wound healing on Wistar rat model. Issue 25 (19th March 2015) - Jaiswal, Maneesh; Gupta, Asheesh; Dinda, Amit Kumar; Koul, Veena
ABSTRACT Semi‐interpenetrating polymeric network hydrogel patches are fabricated using poly(acrylamide) (PAm) and gelatin (G) in which poly(caprolactone) diacrylate is used as a crosslinker for PAm while gelatin is kept uncrosslinked. The healing efficiency of selected hydrogel dressing [PAm1G1(0.5)] is evaluated in comparison with control group (cotton gauze covered with 3M Tegaderm™). The sustained release of gelatin is found to extend from 4 to 15 days while maximum tensile strength stretched to 559 ± 12.5 kPa in PAm1G0.5 matrix, which reduced to 158 ± 6.1 kPa at higher gelatin content (PAm1G1.0). The higher wound contraction (34%), less inflammatory response, significant improvement (P < 0.05) in the collagen biosynthesis, and the granulation tissue formation are observed in PAm/G treated animals in comparison to control, as evidenced by quantitative enhancement of DNA (21%), hydroxyproline (28%), and hexosamine (41%). The histological examination of PAm/G hydrogel treated wound tissues shows enhanced re‐epithelialization on day 8 and 12 post‐wounding, in comparison to control group. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42120.